Meta-Analisis: Pengaruh Integrasi Pendidikan Lingkungan dalam Pembelajaran IPA Terhadap Sikap Peduli Lingkungan Siswa - Yanti, Yuri; Yusliani, Erlina (Jurnal Penelitian Pembelajaran Fisika, 2020)
This study aims to analyze the effect of the integration of environmental education in terms of education levels (elementary, junior high, high school), physical environmental factors (atmosphere, energy, water and humidity) and students' environmental care attitudes in science learning. This research method is a meta-analysis with a sample of 8 articles in national journals and 2 articles in international journals. The instrument used in this study was the code category and the effect size calculation. Based on the results of the study it can be concluded that: 1) the effect of the influence of the integration of environmental education on students' environmental care attitudes at the level of high school education (0.81) is higher than the level of elementary education (0.26) and junior high (0.67); 2) the effect of the integration of environmental education has a high effect on the physical environment factors in the form of the atmosphere (0.81), the moderate effect on environmental physical factors in the form of energy (0.60) and humidity (0.63), and negligible effect on physical environmental factors such as water (0.11); 3) the effect of the integration of environmental education has a moderate effect (0.55) on students' environmental care attitudes in science learning.